What do Cochrane systematic reviews say about diabetic retinopathy? - Mozetic, Vania; Daou, Julia Pozzetti; Martimbianco, Ana Luiza Cabrera; Riera, Rachel (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Diabetic retinopathy is a disease caused by increased permeability of retinal vessels. Its incidence and prevalence have been increasing due to urbanization, greater life expectancy and the habits of modern life. Its onset is insidious and it may lead to blindness in 75% of individuals who have been diabetic for more than 20 years. The aim here was to evaluate the evidence from Cochrane systematic reviews on interventions relating to diabetic retinopathy. DESIGN AND SETTING: Review of systematic reviews, conducted at Cochrane Brazil. METHODS: We included Cochrane systematic reviews on interventions relating to diabetic retinopathy. Two researchers evaluated the inclusion criteria, summarized the reviews and presented the results narratively. RESULTS: Ten reviews met the inclusion criteria. They showed some evidence of benefits from: (a) photocoagulation for diabetic retinopathy; (b) strict glucose and pressure control for postponing the onset of retinopathy; (c) antiangiogenic drugs for macular edema (high-quality evidence); (d) antivascular endothelial growth factor agents for proliferative diabetic retinopathy (very low to low-quality evidence); and (e) intravitreal injection or surgical implantation for treating persistent or refractory macular edema. However, blood pressure control seems to have no benefit after the onset of retinopathy. CONCLUSION: Only a few options are likely to be effective for treating diabetic retinopathy. These include photocoagulation and anti-vascular endothelial growth factor agents. Strict glucose and pressure control seem to postpone the onset of retinopathy. For macular edema, antiangiogenic drugs, intravitreal injection and surgical implantation seem to have some benefit.